Freedom of Expression in Malaysia: Compatibility with the International Human Rights Standard - Saidah Fasihah Binti Che Yussoff; Rohaida Nordin (BESTUUR, 2021)
Malaysia is likely to introduce new laws on freedom of information. However, the important questions are whether the said laws are effective and will have enough bite with the public looking forward to opening government policy. Freedom of information has developed under international human rights law as the right to freedom of expression, including the freedom to seek, receive and impart knowledge and ideas through media, regardless of any frontier. This study aims to examine freedom of expression under the international realm, scrutinize the said freedom in the Malaysian legal framework, and discuss the proposed enactment of freedom of information laws in Malaysia in conformity with international human rights law. This research uses the qualitative research method. This study concludes that freedom of information in Malaysia is severely impeded by the enforcement of the Official Secret Act. This study calls for the repeal or amendment to the Act in conformity with international standards.